Penerapan Model Kooperatif tipe Group Investigation menggunakan media kartu domino dalam upaya meningkatkan proses dan hasil belajar Matematika di kelas IV SD Negeri 225/II Pelepat Lintas - Putri Yulianasari; Randi Eka Putra; Sundahry (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Based on the observation results, the researcher found that 10 out of 16 fourth grade students of SDN 225/II Pelepat Lintas had not achieved KKTP with a percentage of 62.5%. The purpose of this study was to describe the improvement of the cognitive learning process and results with the Group Investigation model using domino card media in fourth grade of SDN 225/II Pelepat Lintas. This study used a Classroom Action Research (CAR) design consisting of four steps, namely: (1) planning, (2) implementation, (3) observation and (4) reflection. The subjects of the study were 16 fourth grade students of SDN 225/II Pelepat Lintas. Data collection techniques used observation, learning outcome tests, and documentation. Data collection instruments used assessments of observation sheets of educators and students and learning outcome test question sheets. The results of the study using the Group Investigation type cooperative model using domino card media can improve students' understanding of the material. Proven by the results of the observation sheet of the educator process which showed an increase in the learning process from cycle I in the good category of 78.5% increasing in cycle II in the very good category of 91%. The results of the assessment of the student learning process also found an increase from the results of the observation sheet in cycle I with a very poor category of 46.5% increasing in cycle II with a good category of 72%. The learning outcomes of students in Mathematics learning using the cooperative model of the Group Investigation type using domino card media in class IV of SD Negeri 225/II Pelepat Lintas showed an increase. In cycle I with the percentage of student learning outcomes reaching 50% which increased to 75% in cycle II.